PENGOLAHAN LIMBAH MINYAK DAN LEMAK DI RESTORAN PADANG DENGAN METODE FISIK (OIL GREASE TRAP) - Ilham Akbar; Ai Silmi (JURNAL TECHLINK, 2021)
One way to process oil and fat wastes is by the physical method of oil grease trap. In principle the oil grease trap method can separate oils and fats using slow speeds. The slow pace would allow time for oil and fat to separate from the water by gravitational force of the oil and fats that had been separated would be contained in container of disposal. The aim of the study is to know the effectiveness of domestic wastewater treatment and how to analyze by means of gravimetric method (SNI 06-6989 10-2011) and to achieve an alternative method of oil and fatty waste treatment. The method used in laboratory studies for testing levels of oil and fats,vcod and TSS that would be compared to p.68/ menlhk/setjen/1/8/2016 on the domestic waste water quality obtained on this study is that oil and fat achieve levels before and after processing as much 18.5 mg/l and 10.1 mg/l with a 45.40% drop. On BOD came levels before and after Processing of 143.88 mg/l and 109.2 mg/l with a 24.10% drop. On COD came levels before and after Processing of 342,32 mg/l and 280,7 mg/l with a 18% drop. On TSS came levels before and after Processing of 188,6 mg/l and 136,32 mg/l with a 27,72% drop. Such results are not yet met by quality standards, so chemical processing of coagulating with poly aluminum chloride and rapid evaporation and flotation with flotation addition is required So that oil and fat, BOD, COD can be reduced.